2011
DOI: 10.1096/fj.11-192997
|View full text |Cite
|
Sign up to set email alerts
|

Opposing roles of RAGE and Myd88 signaling in extensive liver resection

Abstract: In extensive liver resection secondary to primary or metastatic liver tumors, or in living donor liver transplantation, strategies to quell deleterious inflammatory responses and facilitate regeneration are essential. The receptor for advanced glycation endproducts (RAGE) and myeloid differentiating factor 88 (Myd88) are implicated in the inflammatory response. To establish the contributions of RAGE vs. Myd88 signaling in extensive liver resection, we probed the effect of RAGE and/or Myd88, the latter primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 43 publications
5
25
0
Order By: Relevance
“…Much evidence points to lack of direct roles for RAGE in innate/acute immune responses, but, rather, to chronic and tissue-damaging inflammation. Experiments in mice devoid of Ager or Myd88 subjected to massive liver resection (a mechanism to deliver substantial quantities of lipopolysaccharide (LPS) to the liver remnant) revealed that whereas mice devoid of Myd88 succumbed rapidly to massive liver resection, those mice devoid of Ager displayed increased survival and higher levels of activated NF-kB in the remnant, thereby supporting potent anti-apoptotic defense [10]. In mice devoid of both Myd88 and Ager , survival upon massive liver resection was similar to that in mice devoid of Myd88 alone.…”
Section: The Families Of Rage Ligandsmentioning
confidence: 99%
“…Much evidence points to lack of direct roles for RAGE in innate/acute immune responses, but, rather, to chronic and tissue-damaging inflammation. Experiments in mice devoid of Ager or Myd88 subjected to massive liver resection (a mechanism to deliver substantial quantities of lipopolysaccharide (LPS) to the liver remnant) revealed that whereas mice devoid of Myd88 succumbed rapidly to massive liver resection, those mice devoid of Ager displayed increased survival and higher levels of activated NF-kB in the remnant, thereby supporting potent anti-apoptotic defense [10]. In mice devoid of both Myd88 and Ager , survival upon massive liver resection was similar to that in mice devoid of Myd88 alone.…”
Section: The Families Of Rage Ligandsmentioning
confidence: 99%
“…Although Myd88, downstream of certain of the toll-like receptors, is required for survival via regulation of NF-κB and TNF-α, deletion of Ager was associated with significantly higher survival compared to wild-type, Myd88 null, or Ager/Myd88 null mice (Figure 2). Studies performed in the hepatic remnant indicate that RAGE opposes Myd88 signaling by the following mechanisms: (1) RAGE suppresses NF-kB p65 and consequent production of cyclin D1; and (2) RAGE suppresses Pim1 through a STAT3/Il6-mediated mechanism, which will both increase apoptosis and reduce the hyperplasic response [70]. From these studies, we deduced that toll-like receptor signaling was essential for activation of innate mechanisms after massive injury that were required for the animal to survive the acute stress of massive resection of the liver, and that RAGE action blunted the benefits of toll like receptor actions through inhibition of survival mechanisms in the liver, including NF-kB and Pim1.…”
Section: 0 Rage and Roles In Autoimmunity And Chronic Inflammationmentioning
confidence: 99%
“…Our data revealed that although Myd88 was absolutely essential for survival via regulation of NF-κB and tumor necrosis factor–α, only deletion of RAGE significantly improved survival compared to wild-type, Myd88-null, or RAGE-null/Myd88-null mice. Molecular analyses revealed that RAGE opposes Myd88 signaling by multiple mechanisms: first, by suppression of p65 levels, thereby reducing activation of NF-κB and consequent production of cyclin D1; and second, by suppression of interleukin 6–mediated phosphorylation of Stat3, thereby downregulating Pim1 and suppressing the hyperplastic response [71••]. These data affirmed that RAGE was not responsible for immediate survival mechanisms, but, rather, RAGE action amplified inflammation and effectively prevented regeneration in massive liver resection.…”
Section: Perspectivesmentioning
confidence: 99%